(untitled) (Bangladesh Journal of Otorhinolaryngology, 2022)
Background: Salivary gland tumours are relatively uncommon and constitute 3% to 10% of all head & neck neoplasms. The majority of salivary gland tumours arise in the parotid gland. Objectives: To search the clinicopathological presentation of salivary gland tumours. Methods: This was a cross sectional study. Results: The highest incidence of benign tumors was in the 3rd and 4th decade, whereas for malignant tumor it was the 5thdecade of life. Among 47 male patients, 72.3% had benign and 27.7% cases had malignant tumours. Out of 40 female patients 45% cases had benign and 55% cases had malignant tumours. With overall male: female ratio was 1.2:1. Among parotid gland tumours 62.32% had benign and 37.68% cases had malignant tumours. Out of 12 submandibular gland tumours 41.67% cases had benign and 58.33% cases had malignant tumours. Among 35 malignant tumours, 12 Mucoepidermoid carcinoma, the majority occurred in the parotid gland 10(83.3%) followed by submandibular gland 1(8.3%) and minor salivary glands 1(8.3%). Out of 11 cases reported as Adenoid cystic carcinoma, the majority involved submandibular gland 6(54.5%) followed by parotid gland 4(36.4%). Conclusion: Benign salivary gland tumours are more common than malignant ones. There is male preponderance in the incidence of salivary gland tumours. Pleomorphic adenoma is the most frequently encountered tumour among all salivary gland tumours. Bangladesh J Otorhinolaryngol 2022; 28(1): 96-102